A combined approach to correct posterior left ventricular aneurysm, aortic stenosis and coronary artery disease. Issue 10 (12th October 2020) - Patel, Akshay J; Mohamed, Saifullah; Iqbal, Yassir; Kar, Ashok; Soppa, Gopal
Abstract: Ischaemic heart disease and aortic stenosis are potentially life-threatening conditions. A post-infarct left ventricular aneurysm, when combined with the above, is particularly hazardous. We present a case where all three conditions occurred simultaneously and describe the surgical approach undertaken to attempt correction. The patient underwent aneurysmectomy together with aortic valve replacement and two-vessel coronary artery bypass grafting. The aneurysm was excised with direct linear closure of the walls using a Teflon-buttressed interrupted mattress suture technique. Post-operatively, ventricular systolic function was good (LVEF 40%) together with a well-seated aortic valve showing no paravalvular leaks. This case highlights the importance of meticulous removal of thrombus from the aneurysm and everting the edges thereby eliminating a thrombogenic surface and the risk of embolic stroke. The restorative procedure itself serves to underline the importance of ventricular shape in the effective functioning of the myocardium for sustaining an adequate stroke volume with normalized physiology.